Predictive Value of the Serum Cystatin C/Prealbumin Ratio in Combination With NT-proBNP Levels for Long-Term Prognosis in Chronic Heart Failure Patients: A Retrospective Cohort Study - Wang, Chuanhe; Han, Su; Tong, Fei; Li, Ying; Li, Zhichao; Sun, Zhijun (Frontiers in Cardiovascular Medicine, 2021)
Aim: The present study was established to investigate the use of the serum cystatin C/prealbumin (Cys-C/PAB) ratio as a predictive factor for long-term prognosis in patients with chronic heart failure. Methods: We divided our retrospective cohort of 6,311 patients admitted to hospital due to an episode of heart failure (HF) into three groups according to the Cys-C/PAB ratio. The endpoints were cardiovascular and all-cause mortality. Median follow-up time were 3.3 years (2–8 years), during which 2,945 (46.7%) patients died. Results: The Cys-C/PAB ratio was revealed to be an independent predictor of cardiovascular mortality (HR: 1.12, 95% CI: 1.15–1.23, P < 0.01) and all-cause mortality (HR: 1.19, 95% CI: 1.13–1.24, P < 0.01) by multivariable Cox analysis. Integrated discrimination improvement (IDI) showed that the Cys-C/PAB ratio in conjunction with the level of N-terminal pro-B-type natriuretic peptide (NT-proBNP) conferred a significant improvement in predicting individual risks of cardiovascular (P = 0.023) and all-cause (P = 0.028) mortality. For those with a high Cys-C/PAB ratio in combination with a high NT-proBNP level, the long-term cardiovascular mortality risk ratio was 8.6-times higher than for those with low values, and 7.51-times for all-cause mortality. Our study also showed that Cys-C/PAB and NT-proBNP in combination displayed higher value for the prediction of cardiovascular and all-cause in-hospital mortality in patients with HF. Conclusions: The Cys-C/PAB ratio is valuable for predicting cardiovascular and all-cause mortality in patients with HF and offers additional information to that provided by NT-proBNP.